Predictors of University Students’ Feedback Use in a Blended Learning Context - Khue Van Tran; Mai Thi Truc Le (Journal of Learning for Development, 2025)
While engaging with feedback is of significance for learning, current studies have highlighted students’ lack of engagement with feedback. This study aimed at identifying predictors of university students’ feedback use in a blended learning environment based on the extension of the Planned Behaviour Theory. Data were collected via a questionnaire from 374 Vietnamese students who were learning English as a foreign language at a private university in the South of Vietnam. The extension model was tested using partial least square structural equation modelling. The findings revealed that the original model was effective in predicting students’ use of feedback, with attitude and perceived behavioural control as direct predictors of intention, which is an influential factor of students’ use of feedback. It is recommended that educators should employ strategies to enhance self-regulation skills, foster positive attitudes towards feedback, and empower students’ self-efficacy in dealing with feedback, thereby optimising their utilisation of feedback.